Analisis Kontrastif Bentuk Reduplikasi dalam Bahasa Inggris, Bahasa Indonesia, dan Bahasa Jawa - Sholikhati, Nur Indah; Astuti, Nia (STKIP Singkawang, 2024)
This article aims to describe and compare the reduplication rules between English, Indonesian and Javanese using Distributed Reduplication theory. This research is a contrastive analysis research. The object of this research is to reduplicate English, Indonesian, and Javanese. This research was carried out by looking for theoretical sources regarding reduplication and types of reduplication, as well as the data needed to analyze reduplication. This research was conducted using qualitative methods. The results of this research are that it is found that English and Indonesian do not have a form of reduplication like that found in Javanese in the form of repeating the original morpheme twice with phoneme changes (trilingga), pseudo-repetition (lingga semu), repetition of the first syllable (dwipurwa), and repetition of the last syllable (dwiwasana). English does not combine reduplication with affixes, while Indonesian and Javanese use this process. Apart from that, Javanese has a partial form of reduplication with variations in consonant phonemes like repetition in English and Indonesian.